Improvising Machines: Spectral Dance and Token Objects. - Schiemer, Greg (Leonardo Music Journal, 1999)
The author examines the evolution of a system he developed for the creation of two compositions, Spectral Dance and Token Objects, against a backdrop of other composers who have built their own electronic systems. This provides a window on the gradual transformation that has taken place in the way music has been created over the last three decades.